The Effectiveness of Brain Exercises on Reducing Dementia in the Elderly: A Narrative Review - Pelawi, Nitha Esifayona (PROMOTOR, 2024)
Aging in the elderly has an impact on reducing cognitive function, which has implications for dementia. Physical activity carried out by the elderly affects cognitive function, one of which is brain exercise. The purpose of this study was to determine the effectiveness of brain exercises on dementia in the elderly. This research uses a literature study design with databases sourced from PubMed, ScienceDirect, and Google Scholar. Article searches were conducted using the keywords “brain exercise”, “cognitive exercises”, “dementia”, “elderly”, and “effectiveness”. Articles were selected using inclusion and exclusion criteria. The results consistently showed that brain exercise and its variations have a positive effect on cognitive function in the elderly. Implementation of brain exercises can be applied as a strategy for the prevention and management of dementia.